Evaluation of stocking rate, Compudose® implants, and Rumensin® ruminal delivery devices within intensive-early stocking - Cochran, R.C.; Riley, Jack G.; Owensby, Clenton E.; Towne, G.; Vanzant, E.S.; Pope, Ronald V. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Stocking rate in an intensive-early stocking system (1.25, 1.50, or 1.76 acres per steer) did not influence steer gains. Available forage on loamy upland sites was lower after steer removal on July 15 for the highest stocking rate. However, after late season rest, available forage was similar for all stocking rates. Steer gains were consistently greater for groups implanted with Compudose® (estradiol 78β or Compudose plus a Rumensin® (monensin) ruminal delivery device. The Rumensin device alone was successful in increasing average daily gain only at the highest stocking rate.
Keywords: Beef; Compudose®; Rumensin®; Stocking rate; Implants